Regional diversification and inequality between and within regions - Ron Boschma (EconPol Forum, 2022)
The relationship between diversification and wage inequality in regions is still poorly understood. Related diversification is crucial for economic growth of regions. Related diversification in more complex industries tends to increase wage inequality between regions. Related diversification in less complex industries tends to reduce wage inequality. It remains a policy challenge to combine smart and inclusive growth in regions
Keywords: 330